Day 3 Thu, October 18, 2018 2018
DOI: 10.2118/191438-18ihft-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Proppant Flowback through Surface Treatment of Proppant-Laboratory Studies and Field Performance

Abstract: Post stimulation proppant flowback can be a serious problem after the hydraulic fracturing process and can cause a variety of issues like: reduced fracture propping resulting in decreased conductivity and hydrocarbon production;erosion related damage to surface and downhole equipment; and increased costs in dealing with recovered proppant disposal. To address the concerns related to proppant flowback, various technologies, including chemical, mechanical, and engineering design have been employed. A common and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Proppant consolidation additives (PCAs) can enhance the force between proppants and prevent proppant flowback. After a large number of field applications, it was shown that the proppant has a good effect on controlling proppant flowback . Fu et al reported a modified proppant with self-aggregation properties (Figure ).…”
Section: Coated Proppantmentioning
confidence: 99%
See 1 more Smart Citation
“…Proppant consolidation additives (PCAs) can enhance the force between proppants and prevent proppant flowback. After a large number of field applications, it was shown that the proppant has a good effect on controlling proppant flowback . Fu et al reported a modified proppant with self-aggregation properties (Figure ).…”
Section: Coated Proppantmentioning
confidence: 99%
“…After a large number of field applications, it was shown that the proppant has a good effect on controlling proppant flowback. 115 Fu 24 et al reported a modified proppant with self-aggregation properties (Figure 20). After 10 cycles of crushing and polymerization, the strength of the proppant decreased by 54.6%, which could effectively control the flowback of the proppant.…”
Section: Hydrophobic Modification Proppantsmentioning
confidence: 99%